Problemas de linguagem oral e de alimentação: co-ocorrências na clínica fonoaudiológica - Machado, Fernanda Prada (2007)
Background: Speech Therapy studies that concerns about the co-occurrence of feeding and language disorders emphasize the subjective aspects implied. This dissertation has had the objective to examine possible connections between feeding and language disorders, from the bio-psychic perspective. Method: it was carried out a longitudinal analysis of one clinical case aiming to find out and analyze the co-occurrence of feeding and language disorders. For this purpose a literature review about how feeding is dealt with in speech therapy clinics was carried out. Medical theory contributions about feeding and its disorders were also raised. Psychoanalyses theory provided the basis to establish the connections between feeding and language, from the orality concept. Results: the case analyzed was considered as emblematic of connections between feeding and language disorders. Conclusion: results indicate that the importance of functional and physilogical aspects of feeding must not be ignored, but also give advise about the importance of considering the subjective dimension of feeding disorders, given its elemental function